Assembly of gelatin biopolymer to fibrous sepiolite clay for efficient dye removal from wastewater. Issue 48 (5th August 2019) - Sabzi, Mohammad; Shafagh, Nima; Mohammadi, Mohsen
ABSTRACT: This work aimed to fabricate nanocomposites using low‐cost and natural materials for fast and efficient dye adsorption from wastewater. To achieve this, fibrous sepiolite clay was incorporated into the gelatin (GE) biopolymer. The obtained nanocomposites were characterized by Fourier transform infrared spectroscopy and scanning electron microscope techniques. The effects of sepiolite/GE ratio, adsorbent dosage, solution pH, contact time, and initial dye concentration on the adsorption capacity of nanocomposites were well studied and optimized through batch adsorption study. Kinetics, isotherms, and thermodynamics analysis were also performed for methylene blue adsorption. The adsorption data were better fitted with the pseudo‐second‐order and Langmuir isotherm models. The prepared nanocomposites demonstrated a fast and efficient adsorption performance toward the MB dye with the maximum adsorption capacity as high as 684.8 mg g −1 within only an equilibrium time of 30 min, which revealed their promising potential in wastewater treatment. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48266. Abstract :